IMPLEMENTASI PENILAIAN AUTENTIK KOMPETENSI BERBICARA KELAS VII DI SMP NEGERI 1 TERAS - Hidayah, Laila Fitri Nur (2016)
Competence tested in repayment Indonesian is the competence of listening, speaking, reading and writing. In its assessment of competence listening and speaking is difficult because there is no standard provisions regarding aspects assessed. Particularly in the competence to speak only a few KD who have conditions defined in the assessment of aspects that were tested. The purpose of this study to investigate the implementation of authentic assessment and implementation, analyze and find solutions to implementation constraints authentic assessment of competence speak in class VII SMP Negeri 1 terrace. This research was a case study. Researchers are looking for an explanation of the issues, events, or circumstances relating to the implementation of competency assessment speak in class VII SMP Negeri 1 Terrace then researchers look for a solution as the solution of the problem. The data in this study is qualitative. Data analysis techniques used qualitative descriptive. Based on the results of the study, less varied assessment instruments used by subject teachers also contribute to the lack of effective implementation of authentic assessment of competence to speak in SMP Negeri 1 terrace. In fact, not all SK KD generalize all grades aspects tested. Constraints faced directly in the implementation of authentic assessment is the allocation of time. Competence talk takes much as it needs to prepare for the appearance before the vote. In the assessment process, teachers must carefully choose appropriate learning strategies.